2010
DOI: 10.1242/dev.042820
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty2-modulated Kras signaling rescues Shp2 deficiency during lens and lacrimal gland development

Abstract: SUMMARYShp2/Ptpn11 tyrosine phosphatase is a general regulator of the RTK pathways. By genetic ablation, we demonstrate that Shp2 is required for lacrimal gland budding, lens cell proliferation, survival and differentiation. Shp2 deletion disrupted ERK signaling and cell cycle regulation, which could be partially compensated by activated Kras signaling, confirming that Ras signaling was the main downstream target of Shp2 in lens and lacrimal gland development. We also showed that Sprouty2, a general suppressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 37 publications
8
45
0
Order By: Relevance
“…An increasing number of reports have investigated signaling mechanisms governing branching morphogenesis in the early lacrimal gland (Dean et al, 2004;Makarenkova et al, 2000;Pan et al, 2008Pan et al, , 2010Qu et al, 2011;Voronov et al, 2013). These studies have revealed multiple mechanisms underlying the initial development of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of reports have investigated signaling mechanisms governing branching morphogenesis in the early lacrimal gland (Dean et al, 2004;Makarenkova et al, 2000;Pan et al, 2008Pan et al, , 2010Qu et al, 2011;Voronov et al, 2013). These studies have revealed multiple mechanisms underlying the initial development of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry and Histology-Fluorescent immunohistochemistry of cryosections and paraffin sections were performed as described previously (37)(38)(39). The following antibodies were used: mouse anti-Islet1 (1:10), anti-Pax6 (1:10), and anti-Nkx2.2 (1:10) (all from Developmental Studies Hybridoma Bank, Iowa City, IA); mouse anti-Mitf (1:50) (Thermo Scientific, Fremont, CA); rabbit anti-Sox2 (1:800) (Chemicon International, Billerica, MA); rabbit anti-Pax2 (1:100) and rabbit anti-Pax6 (1:250) (both from Covance, Berkeley, CA); rabbit anti-phosphohistone H3 (Ser-10) (1:500) (Upstate, Temecula, CA); and rabbit anti-Ptf1a (1:100) (kindly provided by Dr. Jane E. Johnson, University of Texas Southwestern Medical Center, Dallas, TX).…”
Section: Methodsmentioning
confidence: 99%
“…Secondary antibodies for all experiments were either Alexa Fluor 488-(1:250) or Alexa Fluor 555 (1:500)-conjugated anti-mouse and anti-rabbit IgG (Jackson ImmunoResearch Laboratories, West Grove, PA). For histology of E14.5 paraffin sections of cerebral cortex, hematoxylin and eosin staining was performed as described previously (37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development-Lacrimal gland development is an excellent model for studying the role of heparan sulfate in FGF signaling (29,38,39). Arising from the conjunctival epithelium at the temporal side of the eye, the budding of the lacrimal gland is critically dependent on Fgf10 expressed in the periocular mesenchyme (40,41).…”
Section: Hs2st and Hs6st Are Required For Lacrimal Glandmentioning
confidence: 99%